Management of osteoarthritis: From drug molecules to nano/micromedicines. (6th March 2022) - Di Francesco, Martina; Fragassi, Agnese; Pannuzzo, Martina; Ferreira, Miguel; Brahmachari, Sayanti; Decuzzi, Paolo
Abstract: With the change in lifestyle and aging of the population, osteoarthritis (OA) is emerging as a major medical burden globally. OA is a chronic inflammatory and degenerative disease initially manifesting with joint pain and eventually leading to permanent disability. To date, there are no drugs available for the definitive treatment of osteoarthritis and most therapies have been palliative in nature by alleviating symptoms rather than curing the disease. This coupled with the vague understanding of the early symptoms and methods of diagnosis so that the disease continues as a global problem and calls for concerted research efforts. A cascade of events regulates the onset and progression of osteoarthritis starting with the production of proinflammatory cytokines, including interleukin (IL)‐1β, IL‐6, tumor necrosis factor (TNF)‐α; catabolic enzymes, such as matrix metalloproteinases (MMPs)‐1, ‐3, and ‐13, culminating into cartilage breakdown, loss of lubrication, pain, and inability to load the joint. Although intra‐articular injections of small and macromolecules are often prescribed to alleviate symptoms, low residence times within the synovial cavity severely impair their efficacy. This review will briefly describe the factors dictating the onset and progression of the disease, present the current clinically approved methods for its treatment and diagnosis, and finally elaborate on the main challenges and opportunities for the application of nano/micromedicines in the treatment of osteoarthritis. Thus, future treatment regimens will benefit from simultaneous consideration of the mechanobiological, the inflammatory, and tissue degradation aspects of the disease. This article is categorized under: Nanotechnology Approaches to Biology > Nanoscale Systems in Biology Implantable Materials and Surgical Technologies > Nanotechnology in Tissue Repair and Replacement Abstract :